The Potential of Light Brick from Plywood Industrial Waste as Sound-Absorbing Construction Material - Af'idah, Noer; Wijayadi, Andri Wahyu; Indahwati, Elly (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This research aims to examine the potential of light bricks made from plywood industry waste as a construction material with sound-dampening capabilities. Plywood sawdust waste was chosen as a mixing material due to its abundant availability and its lightweight and porous characteristics, which are expected to enhance the acoustic performance of the bricks. In this study, variations in the composition of plywood powder in bricks were made with the aim of evaluating its effect on physical, mechanical, and acoustic properties. The materials needed for this research are sand, cement, water, and plywood powder. The process of mixing and molding the bricks is done manually. Bricks are dried for 28 days to ensure the mechanical strength and stability of the bricks. Testing was conducted to evaluate physical properties through mass measurement and density testing, mechanical properties through compressive strength testing, and acoustic properties through sound absorption coefficient testing at various frequencies. The research results show that the addition of plywood powder significantly affects the reduction of brick density, making it lighter compared to conventional bricks. Based on the compressive strength test results, it is known that the addition of plywood powder has reduced the compressive strength value of the brick. However, bricks with an additional 10% and 20% volume of plywood powder still meet the minimum compressive strength requirements based on SNI 03-0349-1989. Meanwhile, the results of the sound absorption coefficient test indicate that the increase in the sound absorption coefficient is not significant, presumably due to the structural properties of the bricks that still require porosity optimization. In conclusion, lightt bricks with plywood powder filler have the potential to be environmentally friendly and lightweight construction materials, but they require improvement in optimizing sound absorption for more specific applications in buildings with acoustic insulation needs.